Socio-Technical Innovation Bundles for Agri-Food Systems Transformation - Barrett, Christopher B.; Benton, Tim G.; Fanzo, Jessica; Herrero, Mario; Nelson, Rebecca; Bageant, Elizabeth; Buckler, Edward; Cooper, Karen A.; Culotta, Isabella; Fan, Shenggen; Gandhi, Rikin; James, Steven; et al. (Cornell Atkinson Center for Sustainability and Springer Nature, 2020)
Technological and institutional innovations in agri-food systems (AFSs) over the past century have brought dramatic advances in human well-being worldwide. Yet these gains increasingly appear unsustainable due to massive, adverse spillover effects on climate, natural environment, public health and nutrition, and social justice. How can humanity innovate further to bring about AFS transformations that can sustain and expand past progress, while making them healthier for all people and for the planet that must sustain current and future generations? This report was commissioned by the Cornell Atkinson Center for Sustainability in response to an invitation from the journal Nature Sustainability, which—in collaboration with its new sister journal, Nature Food—wanted to devote its 2020 expert panel to this topic. The panel brought together experts who come from many different continents and who span a wide range of disciplines and organizations—from industry and universities to social movements, governments, philanthropies, institutional and venture capital investors, and multilateral agencies. The panel synthesized the best current science to describe the present state of the world’s AFSs and key external drivers of AFS changes over the next 25–50 years, as well as tease out key lessons from the COVID-19 pandemic experience this year. As is increasingly widely recognized, the costs that farmers and downstream value chain actors incur and the prices consumers pay understate foods’ true costs to society once one accounts for adverse environmental, health, and social spillover effects. Inevitable demographic, economic, and climate change in the coming decades will catastrophically aggravate these problems under business-as-usual scenarios. Innovations will be needed to facilitate concerted, coordinated efforts to transition to more healthy, equitable, resilient, and sustainable AFSs.